(untitled) (European Journal of Pedagogical Initiatives and Educational Practices, 2023)
In the article, the importance of basic and subject-related competencies in solving the problem of professional orientation of teaching Physics is revealed. In addition, it was discussed that practical creativity is necessary for students to explain the nature of physical processes occurring in nature, and to use the knowledge gained from physics in everyday home conditions.